Composite powder and preparation method thereof

By covering the ZrO2 protective shell layer on the surface of WC ceramic particles to form a composite powder, the problems of decarbonization, burning and uneven distribution of WC in laser cladding are solved, and the preparation of high-performance WC particle-enhanced composite coating is realized.

CN119797364APending Publication Date: 2025-04-11TONGLING UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510021624.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

During laser cladding, WC ceramic particles are prone to decarbonization and burning, and are unevenly distributed in the coating due to the difference in density, which easily forms stress concentration and causes cracks.

Method used

A core-shell structure spherical powder with a particle size of 10 to 100 μm is used. The surface of the spherical powder is covered with WC particles of ZrO2 to form a composite powder with an external low-density ZrO2 protective shell layer and an internal WC core particle.

Benefits of technology

It effectively avoids decarbonization and burning of WC during laser cladding, and ensures the uniform distribution of WC in the composite coating, avoids the formation of cracks in the coating, thereby improving the strength of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797364A_ABST
    Figure CN119797364A_ABST
Patent Text Reader

Abstract

The invention discloses composite powder and a preparation method thereof, and belongs to the field of preparation of powder for laser cladding, and the preparation method comprises the following steps: dissolving citric acid and polyvinylpyrrolidone in an ethylene glycol solution, then sequentially adding zirconium nitrate and WC particles, and fully stirring; transferring the mixed solution to a three-neck flask, setting the stirring speed and the heating rate of a heating magnetic stirrer, adding n-butylamine after the reaction temperature is reached, and carrying out constant-temperature reaction for a certain time to obtain a reactant; moving the reactant out of the heating device for cooling, and centrifugally washing and drying the cooled reactant to obtain a precursor product; and carrying out radio frequency plasma spheroidization on the precursor product to obtain the ZrO2-WC composite powder. The preparation method of the composite powder is simple and high in synthesis speed; zrO2-WC composite powder with different densities can be obtained by adjusting process parameters, and the requirements of different parent phase coating reinforced phases are met; according to the method, the problems of decarburization, burning loss and sinking segregation of WC in the laser cladding process are effectively avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a laser cladding material and a preparation method thereof, and in particular to a composite powder for laser cladding and a preparation method thereof. Background Art

[0002] Tungsten carbide (WC) has a high melting point, high hardness and low thermal expansion coefficient, and has good wettability with nickel-based alloys. It is a commonly used ceramic reinforcement phase material for nickel-based alloys. Adding WC ceramic particles to nickel-based alloy powders to reinforce the metal-based ceramic composite coating through laser cladding can organically combine the toughness and good processability of metals with the excellent wear resistance, corrosion resistance, high temperature resistance and oxidation resistance of ceramic materials, and has potential application prospects.

[0003] There are two main problems in the process of laser cladding WC reinforced composite coating: one is the decarburization and burning of WC; the other is the high density of WC (15.63g / cm 3 ), far exceeding the density of the coating parent phase material, will sink to the bottom of the coating in the laser molten pool, resulting in uneven tissue distribution, and the brittle WC ceramic reinforcement phase gathers near the interface to form stress concentration, which will induce coating crack formation. The above two problems greatly affect the performance of laser cladding WC reinforced composite coatings.

[0004] Reinforced ceramic particles with different heat of generation will affect the organization of laser cladding composite coatings. Reinforced phases with smaller heat of generation (such as SiC, etc.) are completely decomposed and evenly dissolved into the parent alloy during the laser cladding process, forming new silicide phases after solidification, and the original SiC particles all disappear, which is equivalent to the effect of laser in-situ self-generated composite coatings; Reinforced phases with larger heat of generation (such as TiC, etc.) are difficult to decompose at high temperatures, and only a small amount of dissolution occurs at the edges of the particles, which basically does not affect the organization of the coating after solidification, and thus are basically retained in the cladding layer after solidification; Reinforced phases with large heat of generation (such as ZrO2, etc.) do not decompose at all during heating, and still retain the original ZrO2 structure. Therefore, if materials with larger or larger heat of generation can be prepared outside the WC, the internal WC can be effectively protected to avoid the decarburization and burning of WC during the laser cladding process. In addition, if the density of the external material is small, by controlling the volume ratio of the low-density protective material to the high-density WC, the density of the composite powder can be made close to the density of the parent phase, thereby solving the problem of the WC reinforcement phase sinking and agglomerating in the laser molten pool due to the large difference in density between the conventional WC reinforcement phase and the parent phase.

[0005] Therefore, it is necessary to develop a composite powder that can solve the problems of decarburization and burning of WC and uneven distribution of WC in the composite coating during laser cladding, and provide a new method for preparing WC composite powder. Summary of the invention

[0006] Purpose of the invention: The purpose of the present invention is to provide a composite powder that can prevent WC decarburization, burning, sinking and segregation during laser cladding. Another purpose of the present invention is to propose a method for preparing the composite powder and solve the problem of how to prepare the composite powder.

[0007] Technical solution: The composite powder described in the present invention is characterized in that it includes spherical powder with a core-shell structure with a particle size of 10 to 100 μm, and the spherical powder is WC particles with ZrO2 coated on the surface.

[0008] The invention has a low-density ZrO2 protective shell layer with large or very high heat of generation on the outside and WC core particles on the inside. The composite powder thus formed can effectively avoid decarburization and burning of WC during laser cladding and can ensure uniform distribution of WC in the composite coating.

[0009] Preferably, the particle size of the WC particles is 1-3 μm, the volume ratio of ZrO2 to WC is 4-5:1, and the density of the spherical powder is 8-9 g·cm -3 .

[0010] In the present invention, the WC particle size is 1-3 μm to prevent agglomeration due to a too small size or sedimentation due to a too large size.

[0011] Another aspect of the present invention discloses a method for preparing the composite powder, comprising the following steps:

[0012] (1) dissolving citric acid and polyvinyl pyrrolidone in ethylene glycol solution, then sequentially adding zirconium salt and WC particles, and fully stirring to obtain a mixed solution;

[0013] (2) stirring and heating the mixed solution, adding n-butylamine after reaching the reaction temperature, and reacting at a constant temperature to obtain a reactant;

[0014] (3) After cooling the reactants, centrifuging and collecting the precipitate, washing and drying to obtain a precursor product; and subjecting the precursor product to radio frequency plasma spheroidization to obtain a ZrO2-WC composite powder.

[0015] Preferably, in step (1), the solid-liquid ratio of citric acid, polyvinyl pyrrolidone and ethylene glycol is 0.1-0.5 g:1.0-5.0 g:100-500 mL.

[0016] Preferably, in step (1), the zirconium salt includes at least one of zirconium nitrate, zirconium chloride, zirconium sulfate, zirconium oxalate and zirconium carbonate.

[0017] Preferably, in step (1), the mass ratio of zirconium salt to WC particles is 10-20:5-15.

[0018] Preferably, in step (2), the stirring and heating condition is a stirring speed of 300-500 r·min -1 , heating rate is 3-5℃·min -1 , the reaction temperature is 170-210℃, and the constant temperature reaction time is 3-5h.

[0019] Preferably, in step (2), the volume ratio of n-butylamine to ethylene glycol is 5-25:100-500.

[0020] Preferably, in step (3), the parameters of the radio frequency plasma spheroidization are: plasma power of 38-42 kW, central gas flow rate of 15-25 L·min -1 , Ar flow rate in sheath gas is 40-60 L·min -1 , the H2 flow rate in the sheath gas is 20-28L·min -1 , carrier gas flow rate is 6-12L·min -1 , powder feeding rate is 0.3-0.7g·min -1 The system pressure is 12-18 kPa. The washing method is to use anhydrous ethanol to wash the precipitate 3-5 times, and the drying condition is vacuum drying at 80-100°C for 6-10 hours.

[0021] The invention further discloses the application of the composite powder in preparing laser cladding coating.

[0022] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:

[0023] 1. In the present invention, the WC particles are coated with ZrO2 with high heat generation, which has a protective effect on the WC particles, effectively avoiding the decarburization and burning problems of WC during the laser cladding process, and laying a foundation for laser cladding of high-performance WC particle-reinforced composite coatings.

[0024] 2. The preparation method of the WC composite powder in the present invention is simple and has a fast synthesis speed. By adjusting the process parameters, the volume ratio of ZrO2 and WC in the composite powder can be regulated, so that ZrO2-WC composite powders of different densities can be obtained to match the requirements of different parent phase coating reinforcement phases. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The external SEM morphology of the ZrO2-WC composite powder prepared in Example 1;

[0026] Figure 2 The internal SEM morphology of the ZrO2-WC composite powder prepared in Example 1;

[0027] Figure 3 for Figure 1XRD analysis results of ZrO2-WC composite powder;

[0028] Figure 4 for Figure 2 EDS analysis results of midpoint A;

[0029] Figure 5 for Figure 2 EDS analysis results of midpoint B. DETAILED DESCRIPTION

[0030] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.

[0031] Example 1: A method for preparing a composite powder is as follows:

[0032] (1) 0.3 g of citric acid and 3.0 g of polyvinyl pyrrolidone were dissolved in 300 mL of ethylene glycol solution, and then 15 g of zirconium nitrate and 10 g of WC particles with a particle size of 1-3 μm were added in sequence, and stirred for 45 min to obtain a mixed solution;

[0033] (2) The mixed solution was then transferred to a three-necked flask and the stirring speed of the heated magnetic stirrer was set to 400 r / min. -1 , Heating rate 4℃·min -1 After the reaction temperature reaches 190°C, 15 mL of n-butylamine is added and the reaction is continued at constant temperature for 4 h to obtain the reactant;

[0034] (3) The reactants were removed from the heating device and cooled. The cooled reactants were washed four times by centrifugation with anhydrous ethanol and dried in a vacuum drying oven at 90°C for 8 h to obtain a precursor product. Finally, a radio frequency plasma spheroidization device with a model number of TekSphero-40 produced by TEKNA of Canada was used to treat the precursor product with the process shown in Table 1 to obtain ZrO2-WC composite powder, and then the powder was screened within the size range required for laser cladding.

[0035] Table 1 RF plasma spheroidization process parameters

[0036] Process parameters <![CDATA[ZrO2-WC composite powder]]> Plasma power / kW 40 <![CDATA[Central gas (Ar) flow rate / L·min -1 > 20 <![CDATA[Sheath gas (Ar) flow rate / L·min -1 > 50 <![CDATA[Sheath gas (H2) flow rate / L·min -1 > 24 <![CDATA[Carrier gas (Ar) flow rate / L·min -1 > 9 <![CDATA[Powder feeding rate / g·min -1 > 0.5 System pressure / kPa 15

[0037] Figure 1 This is the external SEM morphology of the ZrO2-WC composite powder prepared in this example. The powder is spherical and the particle size is about 10 to 100 μm. Figure 2 The internal SEM morphology of the ZrO2-WC composite powder prepared in the example is shown. The composite powder is composed of many WC reinforcement phases with a size of 1 to 3 μm and a coated ZrO2 protective layer. The volume ratio of low-density ZrO2 to high-density WC is about 4:1 to 5:1. The theoretical density of the composite powder is about 8 to 9 g·cm - 3. Figure 3 for Figure 1XRD analysis results of ZrO2-WC composite powder show that it is mainly composed of ZrO2 and WC. Figure 4 and Figure 5 They are Figure 2 The EDS analysis results of area A and area B show that area A is a 1-3μm WC reinforcement phase and area B is a ZrO2 protective layer.

[0038] Example 2: A method for preparing a composite powder is as follows:

[0039] (1) 0.1 g of citric acid and 1.0 g of polyvinyl pyrrolidone were dissolved in 100 mL of ethylene glycol solution, and then 10 g of zirconium sulfate and 5 g of WC particles with a particle size of 1 to 3 μm were added in sequence, and stirred for 45 min to obtain a mixed solution;

[0040] (2) The mixed solution was then transferred to a three-necked flask and the stirring speed of the heated magnetic stirrer was set to 300 r / min. -1 , Heating rate 3℃·min -1 After the reaction temperature reaches 170°C, 5 mL of n-butylamine is added and the reaction is continued at constant temperature for 5 h to obtain the reactant;

[0041] (3) The reactants were removed from the heating device and cooled. The cooled reactants were washed by centrifugation with anhydrous ethanol for 6 times and dried in a vacuum drying oven at 80°C for 10 h to obtain a precursor product. Finally, the precursor product was subjected to a radio frequency plasma spheroidization process with the following parameters: plasma power of 38 kW and central gas flow rate of 15 L min -1 , the Ar flow rate in the sheath gas is 40 L·min -1 , the H2 flow rate in the sheath gas is 20 L·min -1 , carrier gas flow rate is 6L·min -1 , powder feeding rate is 0.3g·min -1 , the system pressure is 12 kPa. That is, ZrO2-WC composite powder is obtained, and then the powder within the size range required for laser cladding is screened.

[0042] Example 3: A method for preparing a composite powder is as follows:

[0043] (1) 0.3 g of citric acid and 3.0 g of polyvinyl pyrrolidone were dissolved in 500 mL of ethylene glycol solution, and then 20 g of zirconium carbonate and 15 g of WC particles with a particle size of 1 to 3 μm were added in sequence, and stirred for 45 min to obtain a mixed solution;

[0044] (2) The mixed solution was then transferred to a three-necked flask and the stirring speed of the heated magnetic stirrer was set to 500 r / min. -1 , Heating rate 5℃·min -1 After the reaction temperature reaches 210°C, 25 mL of n-butylamine is added and the reaction is continued at constant temperature for 3 h to obtain the reactant;

[0045] (3) The reactants were removed from the heating device and cooled. The cooled reactants were washed three times by centrifugation with anhydrous ethanol and dried in a vacuum drying oven at 100°C for 6 h to obtain a precursor product. Finally, the precursor product was subjected to a radio frequency plasma spheroidization process with the following parameters: plasma power of 42 kW and central gas flow rate of 25 L min -1 , Ar flow rate in sheath gas is 60 L·min -1 , the H2 flow rate in the sheath gas is 28L·min -1 , carrier gas flow rate is 12L·min -1 , powder feeding rate is 0.7g·min -1 , the system pressure is 18 kPa. That is, ZrO2-WC composite powder is obtained, and then the powder within the size range required for laser cladding is screened.

[0046] Comparative Example 1: 5.45 g of zirconium oxide with a particle size of 20-50 μm and 15 g of WC particles with a particle size of 1-3 μm were directly mixed and uniformly prepared as a composite powder.

[0047] Comparative Example 2: The rest is the same as Example 1, except that:

[0048] Zirconium nitrate was replaced by titanium nitrate.

[0049] The composite powder samples prepared in Examples 1-3 and Comparative Examples 1-2 were used to prepare laser cladding coatings in the following manner:

[0050] 100mm×100mm×10mm 316L stainless steel was used as the substrate. Ni625 powder and composite powder were mixed evenly at a mass ratio of 3:2 and used as cladding raw powder. The LDF6000 fiber-coupled semiconductor laser from the German LASERLINE company and the KAWASAKI robot were used to prepare the coating on the substrate. The coaxial powder feeding multi-pass overlapping cladding process was adopted. The laser power was 1800W and the laser scanning speed was 420mm·min -1 , powder feeding speed is 2.1r·min -1 The spot diameter is 4 mm, the overlap rate is 50%, and argon is introduced at 20 L min during the test. -1 Gas was used as the protective gas. XRD analysis of the prepared coating revealed the presence of W2C, M 23 C6 and other phases are used to determine whether WC has decarburization and burning during the laser cladding process. The results are as follows:

[0051] Table 2 Effect of different composite powders on WC decarburization and burning in coating

[0052]

[0053] The results in Table 2 show that the present invention can effectively avoid the decarburization and burning of WC during the laser cladding process, avoid cracks in the coating, and effectively improve the strength of the coating. On the one hand, the protective effect of ZrO2 with a large heat of generation in the ZrO2-WC composite powder avoids the decarburization and burning of WC during the laser cladding process. On the other hand, by adjusting the volume ratio of low-density ZrO2 and high-density WC in the composite powder to make the density of the composite powder close to the density of the parent phase powder, it is effectively avoided that the conventional WC reinforcement phase and the parent phase have too large a density difference, which will sink to the bottom of the coating in the laser molten pool, resulting in uneven tissue distribution. The brittle WC ceramic reinforcement phase gathers near the interface to form stress concentration, which will induce the formation of coating cracks, and obtains a high-performance composite coating with uniform reinforcement phase distribution and no cracks in the composite coating. In Comparative Example 1, since ZrO2 and WC are not compounded to form a core-shell structure, the independent ZrO2 cannot inhibit the decarburization and burning of WC, nor can it reduce the density of the composite powder, resulting in the WC particles still being deposited at the bottom of the coating, thereby generating cracks. Therefore, the compressive strength of the coating of Comparative Example 1 is significantly lower than that of Examples 1-3.

Claims

1. A composite powder, characterized in that: The invention comprises spherical powder of core-shell structure with a particle size of 10-100 μm, wherein the spherical powder is WC particles with ZrO2 coated on the surface.

2. The composite powder according to claim 1, characterized in that: The particle size of the WC particles is 1-3 μm, the volume ratio of ZrO2 to WC is 4-5:1, and the density of the spherical powder is 8-9 g·cm -3 .

3. The method for preparing the composite powder according to claim 1 or 2, characterized in that: The steps include: (1) dissolving citric acid and polyvinyl pyrrolidone in ethylene glycol solution, then sequentially adding zirconium salt and WC particles, and fully stirring to obtain a mixed solution; (2) stirring and heating the mixed solution, adding n-butylamine after reaching the reaction temperature, and reacting at a constant temperature to obtain a reactant; (3) cooling the reactants, centrifuging and collecting the precipitate, washing and drying to obtain the precursor product; The precursor product is spheroidized by radio frequency plasma to obtain ZrO2-WC composite powder.

4. The method for preparing the composite powder according to claim 3, characterized in that: In step (1), the solid-liquid ratio of citric acid, polyvinyl pyrrolidone and ethylene glycol is 0.1-0.5 g:1.0-5.0 g:100-500 mL.

5. The method for preparing the composite powder according to claim 3, characterized in that: In step (1), the zirconium salt includes at least one of zirconium nitrate, zirconium chloride, zirconium sulfate, zirconium oxalate and zirconium carbonate.

6. The method for preparing the composite powder according to claim 3, characterized in that: In step (1), the mass ratio of zirconium salt to WC particles is 10-20:5-15.

7. The method for preparing the composite powder according to claim 3, characterized in that: In step (2), the stirring and heating conditions are as follows: the stirring speed is 300-500 r·min -1 , heating rate is 3-5℃·min -1 , the reaction temperature is 170-210℃, and the constant temperature reaction time is 3-5h.

8. The method for preparing the composite powder according to claim 3, characterized in that: In step (2), the volume ratio of n-butylamine to ethylene glycol is 5-25:100-500.

9. The method for preparing the composite powder according to claim 3, characterized in that: In step (3), the parameters of RF plasma spheroidization are: plasma power of 38-42 kW, central gas flow rate of 15-25 L·min -1 , Ar flow rate in sheath gas is 40-60 L·min -1 , the H2 flow rate in the sheath gas is 20-28L·min -1 , carrier gas flow rate is 6-12L·min -1 , powder feeding rate is 0.3-0.7g·min -1 , the system pressure is 12-18kPa.

10. Use of the composite powder according to claim 1 or 2 in preparing laser cladding coatings.